The Relationship Between Interpersonal Comunication Skills and Job Satisfaction Of Social Services in The Tanah Datar Districts - Fiona Rahma Zona; Taufik Taufik (Jurnal Neo Konseling, 2019)
This research is motivated by the phenomenon such as employees who are less supportive among fellow employees, employees who are less concerned and less supportive among fellow employees, employees who distinguish positions in interacting and discussing in the office environment, employees who are not serious about hearing other employees in speaking and there are employees who do not respect the opinions of their friends. One of the causes of low employee job satisfaction is allegedly due to lack of interpersonal communication skills. This study aims to examine the relationship between interpersonal communication skills with employee job satisfaction. This type of research is a correlational descriptive study with quantitative methods. Subjects in this study were 38 employees of the Tanah Datar district social service. Collected using a scale questionnaire to measure interpersonal communication variables and job satisfaction variables. Data were processed using the Pearson Product Moment formula with the Statistical Product and Service Solution (SPSS) program version 20.0. There is a low relationship between interpersonal communication with job satisfaction.